Covid-19 and simplification of urban planning tools. The residual plan - Boschetto, Pasqualino (TeMA - Journal of Land Use, Mobility and Environment, 2020)
This paper aims to develop an initial reflection on the Residual Plan can be. The Urban Plan has always coincided with the offer of public power, leaving deliberately aside the continuous ’dynamic of the real’, mainly coming from the private component of our society (The demand plan). In the transition from Modern to Postmodern, the environmental question undermined the consolidated certainties of the Offer Plan; opening up increasingly consistent operational gaps with the Residual Plan, which could represent the urban plan coherent with Postmodernism. Covid-19 is further complicating the fate of the Urban Plan, increasingly complex, uncertain and unable to regenerate itself according to the new paradigms of the organization of the territory. In this sense, at least in the Covid-19 transitional period, the Residual Plan could be experimented to understand its real capability of answering to the dynamics of the organization of the territory.